2000
DOI: 10.1038/sj.bmt.1702659
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary relapse after allogeneic bone marrow transplantation for haematological malignancy

Abstract: Summary:We describe the risk factors for and the natural history and response to treatment of extramedullary (EM) relapse in 183 patients who underwent allogeneic bone marrow transplantation (alloBMT) for a variety of haematological malignancies at our institution over a 7. year period. Fifty-one patients relapsed; 15 had EM relapse either alone or in association with marrow involvement. A retrospective analysis found that the presence of chronic GVHD and a longer interval between transplant and relapse were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
84
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 14 publications
8
84
0
Order By: Relevance
“…In addition, several of the relapses presented at unusual extramedullary sites, a phenomenon described before in conjunction with DLI. [35][36][37][38][39] Together, these observations are compatible with the notion that immune intervention may have influenced the timing and presentation of leukemia recurrence. Strong indications for the presence of immunological pressure on leukemic AML cells by the emergence of HLA loss variants have been recently reported.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, several of the relapses presented at unusual extramedullary sites, a phenomenon described before in conjunction with DLI. [35][36][37][38][39] Together, these observations are compatible with the notion that immune intervention may have influenced the timing and presentation of leukemia recurrence. Strong indications for the presence of immunological pressure on leukemic AML cells by the emergence of HLA loss variants have been recently reported.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, a large study of extramedullary relapse of haematological malignancies following allogeneic transplantation included three cases of isolated soft-tissue plasmacytoma occurring between 30 and 51 months post-transplant in patients with multiple myeloma. 8 This study suggested that extramedullary relapse was relatively resistant to graft-versus-tumour effects with poor responses to DLI. These data are in keeping with a report by Zomas et al 6 who described a patient treated with DLI for frank marrow relapse post allogeneic transplant in whom there was complete response of the systemic disease but the patient subsequently went on to develop subcutaneous plasmacytomas.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature suggests that similar localised or extramedullary relapse has been observed by several other authors after allogeneic transplantation for myeloma and may, in fact, be a frequent finding. [4][5][6][7][8][9] Patients and methods A total of 25 patients who received allogeneic transplants from matched-sibling donors for multiple myeloma (n ¼ 23) or plasma cell leukaemia (n ¼ 2) in a single centre from 1991 to 2000 were studied. Patient characteristics are shown in Table 1.…”
mentioning
confidence: 99%
“…This is not only reported for MM, but also for acute leukaemias. 15,16 These EM relapses are believed to indicate transformation of the disease, associated with a more aggressive behaviour, therapy resistance and short survival. However, reports regarding this subject in MM are lacking data on the efficacy of the relapse treatment or are case reports.…”
Section: Discussionmentioning
confidence: 99%